Ozone exchange within and above an irrigated Californian orchard. Issue 1 (1st January 2020) - Brown, J.S.; Shapkalijevski, M.M.; Krol, M.C.; Karl, T.; Ouwersloot, H.G.; Moene, A.F.; Patton, E.G.; Vilà-Guerau de Arellano, J.
Abstract: In this study, the canopy effects on the vertical ozone exchange within and above Californian orchard are investigated. We examined the comprehensive dataset obtained from the Canopy Horizontal Array Turbulence Study (CHATS). CHATS typifies a rural central Californian site, with O3 mixing ratios of less than 60 ppb and moderate NO x mixing ratios. The CHATS campaign covered a complete irrigation cycle, with our analysis including periods before and after irrigation. Lower O3 mixing ratios were found following irrigation, together with increased wind speeds, decreased air temperatures and increased specific humidity. Friction velocity, sensible heat and gas fluxes above the canopy were estimated using variations on the flux-gradient method, including a method which accounts for the roughness sublayer (RSL). These methods were compared to fluxes derived from observed eddy diffusivities of heat and friction velocity. We found that the use of the RSL parameterization, which accounts for the canopy-induced turbulent mixing above the canopy, resulted in a stronger momentum, heat, and ozone exchange fluxes above this orchard, compared to the method which omits the RSL. This was quantified by the increased friction velocity, heat flux and ozone deposition flux of up to 12, 29, and 35% at 2.5 m above the canopy, respectively. Within the canopy, vertical fluxes, as derived from local gradients and eddy diffusivity of heat, were compared to fluxes calculated using the Lagrangian inverse theory. Both methods showed a presence of vertical flux divergence of friction velocity, heat and ozone, suggesting that turbulent mixing was inefficient in homogenizing the effects driven by local sources and sinks on vertical exchange of those quantities. This weak mixing within the canopy was also corroborated in the eddy diffusivities of friction velocity and heat, which were calculated directly from the observations. Finally, the influence of water stress on the O3 budget was examined by comparing the results prior and after the irrigation. Although the analysis is limited to the local conditions, our in situ measurements indicated differences in the O3 mixing ratio prior and after irrigation during CHATS. We attribute these O3 mixing ratio changes to enhanced biological emission of volatile organic compounds (VOCs), driven by water stress.